2017
DOI: 10.1186/s12879-017-2591-6
|View full text |Cite
|
Sign up to set email alerts
|

Urinary schistosomiasis among vulnerable children in a rehabilitation home in Ibadan, Oyo state, Nigeria

Abstract: BackgroundSchistosomiasis is a disease of public health importance with long term complications mostly common among children, rural dwellers, poor and migrant workers. Studies have not documented the burden among migrant workers and their families. The study aimed to describe the burden of schistosomiasis and demographic characteristics among children of migrant workers residing in a rehabilitation home in Ibadan, Nigeria.MethodsA cross-sectional study using sixty six children, who were tested following compla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
3
11
0
Order By: Relevance
“…(2014) , who recorded higher prevalence in males. It was also observed to be more prevalent in older children supporting the reports of Federal Ministry of Health (2015) and Uchendu et al. (2017) in Nigeria; and Ntonifor et al.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…(2014) , who recorded higher prevalence in males. It was also observed to be more prevalent in older children supporting the reports of Federal Ministry of Health (2015) and Uchendu et al. (2017) in Nigeria; and Ntonifor et al.…”
Section: Discussionsupporting
confidence: 80%
“…Approximately 90% of the cases occur in Africa of which nearly two-thirds are caused by S. haematobium ( Hotez and Kamath, 2009 ; Vos et al., 2012 ). Nigeria has the highest prevalence among the 75 countries in which the disease is endemic ( Uchendu et al., 2017 ; WHO, 2019b ). In Nigeria, a prevalence of 9.5% was reported by the Federal Ministry of Health (2015) .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, prevalence of infection varies from 8.9% to 28.7%. This is similar to many reports in Nigeria (Atalabi et al, 2017;Uchendu et al, 2017) and other countries (Dahab and El-Bingawi, 2012;Negussu et al, 2013). The reports from Sokoto, Nigeria (Singh et al, 2016), Ethiopia (Geleta et al, 2015) and Senegal (Senghor et al, 2014) revealed considerable higher prevalent rates.…”
Section: Discussionsupporting
confidence: 90%
“…S. haematobium infection in Nigeria varies between 2 to 90%, of which most cases occur among school-going children and those with very low socioeconomic status [12,20]. Although, in Osun and Kwara State, urinary schistosomiasis has been studied and reported to some extent in several rural and peri-urban communities [21][22][23][24][25], however, these studies are not sufficient to determine the factors affecting the distribution of urinary schistosomiasis in these areas. Moreover, there is an urgent need for updated epidemiological information that can enhance the management, control and prevention of urinary schistosomiasis in Osun and Kwara State.…”
Section: Introductionmentioning
confidence: 99%